2021
DOI: 10.17241/smr.2021.00969
|View full text |Cite
|
Sign up to set email alerts
|

Later Chronotype Correlates With Severe Depression in Indonesian College Students

Abstract: Background and Objective The correlation between late chronotype and depression has been well documented, but reports from the equatorial area, where the sun shines throughout the year with less seasonal variation, are limited. In the present research study, we sought to 1) examine the relationship between the chronotype and mental health symptoms in an Indonesian student population and 2) explore the characteristics of those who lie at the extreme chronotype and psychometry.Methods This is a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Similar conclusions have been made in the studies by Romo-Nava who observed that female academic stress and evening chronotype were the factors associated with an increased risk of developing a depressive episode [ 64 ]. Additionally, Supit et al have demonstrated that people with an evening chronotype are more likely to have a high depression score [ 65 ]. Gorgol et al came to similar conclusions, observing that high neuroticism, low conscientiousness, and low alpha stability are the factors that increase this risk, especially among the evening chronotypes [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions have been made in the studies by Romo-Nava who observed that female academic stress and evening chronotype were the factors associated with an increased risk of developing a depressive episode [ 64 ]. Additionally, Supit et al have demonstrated that people with an evening chronotype are more likely to have a high depression score [ 65 ]. Gorgol et al came to similar conclusions, observing that high neuroticism, low conscientiousness, and low alpha stability are the factors that increase this risk, especially among the evening chronotypes [ 66 ].…”
Section: Discussionmentioning
confidence: 99%